ACCORDING TO TEACHERS’ VIEWS PROBLEM SOLVING COMPETENCIES BY MANAGERS WHO WORK IN FINE ARTS AND SPORT HIGH SCHOOLS - Çoban, Bilal; Karademir, Tamer; Devecioğlu, Sebahattin; Karakaya, Yunus Emre (Kastamonu Üniversitesi, 2011)
In this study, in line views of teachers proficiency in problem solving of the managers who served in Fine Arts and Sports College which started from 2004 to 2005 academic years was researched. The sample group of the research has been constituted by branch teachers who work in Fine Arts and Sport High School in the province of Elazig, Usak, Malatya, Trabzon, Eskisehir and Corum. As a result of the research, in terms of gender, education, age and variables of occupational experience and significant differences were seen among the opinions of physical education teachers. Creating positive interaction between school staff and the manager in these institution,perceiving positively by all teachers for problem solving methods applied was considered an important factor in removing to the highest level of quality of education.

Bu çalışmada, 2004-2005 eğitim-öğretime başlayan Güzel Sanatlar ve Spor Liselerinde görev yapan yöneticilerin öğretmen görüşleri doğrultusunda problem çözme yeterlikleri araştırılmıştır. Araştırmanın örneklemini Elazığ, Uşak, Malatya, Trabzon, Çorum ve Eskişehir illerinde bulunan Güzel Sanatlar ve Spor Lisesinde görev yapan 128 branş öğretmeni oluşturmaktadır. Araştırma sonucunda cinsiyet, eğitim, mesleki deneyim, yaş ve hizmet süresi değişkeni bakımından öğretmen görüşleri arasında anlamlı farklılıklar görülmüştür. Bu kurumlarda yönetici ve okul çalışanları arasında pozitif etkileşimlerin oluşturulması, problemlerin çözümü için başvurulan yöntemlerin bütün öğretmenler tarafından olumlu algılanması, eğitim kalitesinin en üst düzeye çıkarılmasında önemli bir faktör olarak değerlendirilmiştir
ÖĞRETMEN GÖRÜŞLERİNE GÖRE GÜZEL SANATLAR VE SPOR LİSELERİNDE GÖREV YAPAN YÖNETİCİLERİN PROBLEM ÇÖZME YETERLİKLERİ